Study of association between characteristics of patient and likelihood of benzodiazepine use in psychiatry outpatient department at tertiary care hospital of Kathmandu - Raut, Binod; Khadka, Anjan; Manandhar, Pradeep; Kandel, Kamal (Journal of Chitwan Medical College, 2017)
Introduction: Benzodiazepines exert their pharmacological properties as hypnotics, anxiolytics, anticonvulsants and muscle relaxants. Benzodiazepines are clinically effective for a number of indication including the reduction of anxiety, the induction and maintenance of sleep, muscle relaxation. They have a range of well documented adverse effects that may outweigh the benefits in certain patient population including psychomotor impairment, development of tolerance and dependence, potential for abuse. Methods: It is a hospital based prospective cross-sectional study conducted in a psychiatry outpatient department of tertiary care hospital. All the patients attended to the outpatient department of psychiatry and prescribed with benzodiazepine were selected for study. Drug therapy details in medication chart review and clinical review in patients treated with benzodiazepines was analyzed to measure the utilization pattern of benzodiazepines in terms of patient characteristics (e.g. age, gender and marital status), occupation, education and diagnosis, number of prescription of benzodiazepines, their doses, frequency, routes of administration and duration of use in each patient. Results: Out of a total of 384 patients, 246 of the patients had been currently using at least one benzodiazepine. Prevalence of benzodiazepine use was 64%. There was statistically significant association between benzodiazepines use with gender distribution, occupation and education. The prevalence of benzodiazepines use is relatively higher than that reported in the developed countries. Clonazepam was the most widely used benzodiazepine followed by lorazepam. Conclusion: The study evaluated the association between characteristics of patient and likelihood of benzodiazepines use. This will definitely help to optimize the drug therapy, improve the quality of care and reduce the negative outcomes in the usage of benzodiazepines.